Correlates of blood pressure in community-dwelling older adults. The Cardiovascular Health Study. Cardiovascular Health Study (CHS) Collaborative Research Group. - Tell, G S; Rutan, G H; Kronmal, R A; Bild, D E; Polak, J F; Wong, N D; Borhani, N O (Hypertension, 1994)
Although elevated blood pressure is an important predictor of cardiovascular disease and stroke in the elderly, little information exists on the distribution and risk factor correlates of blood pressure in this group. As part of the Cardiovascular Health Study, a population-based cohort study of 5201 men and women aged 65 to 101 years, we investigated correlates of systolic and diastolic blood pressure. Multiple regression analyses were conducted for all participants and a subgroup of 2482 without coronary heart disease and not on antihypertensive therapy (the "healthier" subgroup). In the total group, independent predictors of diastolic blood pressure included heart rate, aortic root dimension, creatinine, hematocrit, alcohol use, and black race (positive associations) and internal carotid artery wall thickness, mitral early/late peak flow velocity, white blood cell count, cigarette smoking, and age (negative associations). Positive predictors of systolic blood pressure included mitral late peak flow velocity, left ventricular mass, common carotid artery wall thickness, serum albumin, factor VII, diabetes, alcohol use, and age; negative predictors were coronary heart disease, uric acid, height, and smoking. In the healthier subgroup, positive predictors of diastolic blood pressure included heart rate, hematocrit, serum albumin, creatinine, and body weight, whereas mitral early/late peak flow velocity, serum potassium, smoking, and age inversely related to diastolic pressure. For the same group, common carotid artery wall thickness, left ventricular mass, serum albumin, factor VII, high-density lipoprotein cholesterol, and age were directly related to systolic blood pressure, whereas serum potassium was inversely related. Both systolic and diastolic pressures varied considerably by geographic site.(ABSTRACT TRUNCATED AT 250 WORDS)
Keywords: Aged; Aged, 80 and over; Aging; Blood Pressure; Cohort Studies; Coronary Disease; Female; Health Surveys; Humans; Hypertrophy, Left Ventricular; Male; Regression Analysis; United States

Compensatory increase in common carotid artery diameter. Relation to blood pressure and artery intima-media thickness in older adults. Cardiovascular Health Study. - Polak, J F; Kronmal, R A; Tell, G S; O'Leary, D H; Savage, P J; Gardin, J M; Rutan, G H; Borhani, N O (Stroke, 1996)
BACKGROUND AND PURPOSE: Common carotid artery (CCA) diameter is thought to increase as a consequence of hypertension and may increase as the thickness of the arterial wall increases. The purpose of this study was to determine CCA dimensions and correlate them with clinical features. METHODS: We performed a cross-sectional, community-based study of adults 65 years of age and older, measuring inner and outer diameter of the CCA in vivo with carotid sonography. Findings were correlated against risk factors for atherosclerosis, CCA intima-media thickness (IMT), and echocardiographically determined left ventricular (LV) mass. RESULTS: Independent variables showing strong positive associations with outer and inner CCA diameter included age, male sex, height, weight, and systolic blood pressure. As an independent variable, LV mass (r = .40 and r = .37, respectively; P < .00001) had a strong positive relation to inner and outer CCA diameters. The relationship between diameter and IMT was different. In a model that controlled for age, sex, and estimated LV mass, an increase of 1 mm in CCA IMT corresponded to a 1.9 mm increase in the outer diameter of the artery (P < .00001) but was not significantly related to the inner diameter (slope = +0.07 mm; P = .26). CONCLUSIONS: Increase in the outer diameter of the CCA is associated with subject size, sex, age, echocardiographically estimated LV mass, and CCA IMT. Increases in internal diameter of the CCA have similar relationships but are not related to IMT. This supports the hypothesis that the human CCA dilates as the thickness of the artery wall increases.
Keywords: Aged; Blood Pressure; Carotid Artery, Common; Cross-Sectional Studies; Echocardiography; Female; Heart Ventricles; Humans; Hypertension; Male; Tunica Intima; Tunica Media

Carrying the burden of cardiovascular risk in old age: associations of weight and weight change with prevalent cardiovascular disease, risk factors, and health status in the Cardiovascular Health Study. - Harris, T B; Savage, P J; Tell, G S; Haan, M; Kumanyika, S; Lynch, J C (Am J Clin Nutr, 1997)
Measured weight in old age, reported weight at age 50 y, and weight change from age 50 y to old age were studied in association with prevalent cardiovascular disease (CVD), CVD risk factors, and health status in a population of 4954 men and women aged > or = 65 y in the Cardiovascular Health Study (CHS). Heavier weight (i.e., generally weight in the fourth quartile for the cohort) at age 50 y was more closely associated with prevalent CVD than was current weight, with these associations stronger in women than in men. Heavier current weight and heavier weight at age 50 y were associated with cardiovascular risk factors, including higher blood pressure, lower high-density-lipoprotein cholesterol, and higher fasting insulin. Heavier weight at both time points was related to mobility problems in both men and women and to lower current physical activity levels; among women, strong associations were also seen with lower education and current income. Remaining within 10% of reported weight at age 50 y was associated with better health status as measured by reported health, mobility difficulty, number of medications, and prevalent CVD in men. Paradoxically, most cardiovascular risk factors were lowest for weight losers despite an association of weight loss with poorer health. In this cohort of persons aged > or = 65 y, heavier weight was associated with CVD and CVD risk factors, suggesting that prevention of overweight may prove beneficial in improving cardiovascular risk in older persons. Weight stability from age 50 y to old age was associated with better health status than was weight gain or loss.
Keywords: Aged; Blood Pressure; Body Constitution; Body Weight; Cardiovascular Diseases; Cholesterol, LDL; Female; Health Status; Humans; Insulin; Longitudinal Studies; Male; Middle Aged; Odds Ratio; Prevalence; Risk Factors; Sex Characteristics